13. Integrating Functions of Music in Learning and Education - Morari Marina (Sciendo, 2022)
Isolation/separation of human activity from art is a manifestation of the incoherence of our society. In scientific research, the spiritual and physical worlds are often separated. In the recovery of this dualism in the education system, but also the life of human society, an organic place must be occupied by the arts. Because it is only in the work of art that we find the expression of the human inner world, which naturally connects human life with the environment - the external world in which the artist lives/creates. Integrated education and learning are based on quality disciplinary education. The article develops the integrative functions of musical art in the process of school learning and early education and identifies the levels of musical-didactic activities integration in the educational process.